Estimación de la huella hídrica en el Centro de Gestión y Desarrollo Sostenible Surcolombiano, sede Yamboró - Patiño Villarraga, Andrea
The phenomena of climate change, caused by anthropic and natural actions, have triggered a watercrisis, which puts at risk the sufficiency of the resource to meet the basic needs of the populationsand the development of productive processes. These alterations are increasing the fragility of aquaticecosystems; therefore, sustainable development mechanisms should be implemented with anefficient water management approach. The objective of this research was to estimate the waterfootprint generated by the activities carried out at the Surcolombiano Management and SustainableDevelopment Center, Yamboró headquarters. The methodology applied to calculate the waterfootprint was the one proposed by Hoesktra in the Water Footprint Assessment Manual establishedas a world standard, which establishes the determination of the direct WF from three aspects: blueWF, green WF and gray WF. To calculate the green WF, the green area and the effective precipitationwere considered; To evaluate the blue WF, the volume of drinking water and the water that returnsto the water source through discharges were taken. For the calculation of the gray water footprint,the COD parameter was taken as an indicator, as well as the volumes of the influent and effluent.These indicators estimated from the WF of the Yamboró headquarters will allow management for thecomprehensive use of water in the activities carried out within the institution, by reducingconsumption, creating factors of sustainability and use of water resources